Microemulsion - A Chemical Nanoreactor [Working Title] 2019
DOI: 10.5772/intechopen.84295
|View full text |Cite
|
Sign up to set email alerts
|

Pseudophase Model in Microemulsions

Abstract: The kinetic behaviours in microemulsions can be easily modelled using an extension of the pseudophase model previously developed for micellar catalysis. This model considers that the microheterogeneous media can be considered as the sum of different conventional reaction media, where the reagents are distributed and in which the reaction can occur simultaneously. The reaction rate observed in the microheterogeneous system will be the sum of the velocities in each one of the pseudophases. This use can be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Cao et al [ 29 ] reported using an ionic surfactant, sodium di-2-ethyl hexyl sulfosuccinate [ 30 , 31 , 32 ] (AOT), to activate or charge PS nanoparticles of different sizes: 141, 311, and 535 nm. The behavior of nanoplastics showed that the PS/AOT/water system’s charging mechanism was adsorption-dominated, revealing the importance of the association between the activation of the particle surfaces and particle charging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al [ 29 ] reported using an ionic surfactant, sodium di-2-ethyl hexyl sulfosuccinate [ 30 , 31 , 32 ] (AOT), to activate or charge PS nanoparticles of different sizes: 141, 311, and 535 nm. The behavior of nanoplastics showed that the PS/AOT/water system’s charging mechanism was adsorption-dominated, revealing the importance of the association between the activation of the particle surfaces and particle charging.…”
Section: Methodsmentioning
confidence: 99%
“…Cao et al [ 29 ] assessed the charge-mediating of PSNPs using AOT surfactant in aqueous solutions [ 30 , 31 , 32 ]. PSNPs were obtained with three different sizes: 141, 311, and 535 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Under a given (fixed) set of experimental conditions, an equilibrium is established between ions located in the interfacial region of the emulsion (bounded ions) and the remaining ions in the aqueous phase. This two-site model has been proved experimentally in micellar systems by employing different experimental techniques that quantitatively measure either bound-or free-ion concentrations [40][41][42][43] and should also be applicable to emulsions because emulsion droplets and micelles are present simultaneously and typically exchange material at diffusion-controlled rates [21,[44][45][46]. Thus, in emulsions formed with a surfactant with counterions X with charge Zx and containing other counterions Y with charge Zy, the equilibrium condition for each counterion requires that the electrochemical potentials of aqueous and bounded counterions be equal to each other, and the ion-exchange constant given by Equation (1) can be derived [13,15,43,47].…”
Section: An Overview Of the General Effects Of Charged Interfaces On ...mentioning
confidence: 99%
“…At cationic interfaces, the exchange is described by an empirical Donnan equilibrium constant between H + and Br − [41,42]. Within cationic interfaces, the interfacial H + concentration may be significantly lower, by one to two orders of magnitude, than the bulk [H + ].…”
Section: An Overview Of the General Effects Of Charged Interfaces On ...mentioning
confidence: 99%
“…The compartmentalization of reactants in reverse micelles is a key aspect of their utility in various chemical and biochemical applications. The localization of reactants gives rise to catalytic effects on the rates of the reactions, thereby controlling the kinetics and mechanism of reactions (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%